Functional properties of chickpea protein-pectin interfacial complex in buriti oil emulsions and spray dried microcapsules - Moser, Poliana [UNESP]; Nicoletti, Vania Regina [UNESP]; Drusch, Stephan; Brueckner-Guehmann, Monika (Elsevier B.V., 2020)
The aim of the present study was to investigate the impact of chickpea protein (CP) alone or in the form of sequentially adsorbed chickpea protein and high methoxylated pectin (CP-HMP) on the microencapsulation of buriti oil by spray drying. CP was extracted and characterized by its molecular weight distribution, zeta potential and solubility. The adsorption of CP and CP-HMP complexes to the oil/water (O/W) interface was investigated by measurement of the interfacial tension. The interactions between the molecules at the O/W interface were analyzed by interfacial shear rheology. Emulsions containing CP or CP-HMP were prepared at pH 3.5, homogenized and spray dried at 180/70 degrees C and 210/90 degrees C (inlet/outlet) temperature. The oil droplet size distribution (ODS) of emulsions before and after spray drying, the encapsulation efficiency (EE) of microcapsules and their oxidative stability were evaluated. The interfacial tension of CP at the O/W interface was not affected by pectin addition. However, interfacial shear rheology revealed strong interactions between CP-HMP complexes, maintaining the physical integrity of emulsion oil droplets during spray drying. On the other hand, interactions in the CP film were weaker and the droplets were affected by spray drying, suffering from an increase in size. The EE of CP-HMP microcapsules was higher than for CP microcapsules, which suggests a synergistic effect. The spray drying temperature had no effect on the EE. During 6 months of storage, a slight increase of the conjugated dienes content was observed for all microcapsules. However, the type of microcapsule and the temperature of spray drying had no effect on the development of lipid oxidation.
Keywords: Chickpea protein; Pectin; Interfacial shear rheology; Spray drying; Microencapsulation; Oxidative stability